Ecosistemas: seguimos creciendo - Rodríguez-Echeverría, Susana; Alonso, Alvaro; Amoroso, Mariano; Blanco, Juan A.; Lacerot, Gisselle; Molina-Morales, Mercedes; Puerta-Piñero, Carolina; Vargas-Rodríguez, Renzo; Jiménez-Eguizabal, Leyre (Ecosistemas, 2017)
Rodríguez-Echeverría, S., Alonso, Á., Amoroso, M., Blanco, J.A., Lacerot, G., Molina-Morales, M., Puerta-Piñero, C., Vargas-Rodríguez, R., Jiménez-Eguizabal, L. 2017. Ecosistemas: seguimos creciendo. Ecosistemas 26(1): 86-87. Doi.: 10.7818/ECOS.2017.26-1.11